Pengaruh e-s-qual terhadap loyalitas menggunakan aplikasi gojek pada masyarakat kota Padang - Wardi, Yunia; Engriani, Yunita; Putra, Ridho Sunella (Jurnal Kajian Manajemen Bisnis, 2019)
The main need of this research is to see the effect of the quality of electronic services (E-S-Qual) on customer loyalty using the online transportation application (Gojek) in the city of Padang. This type of research is causally comparative. This research was conducted in the city of Padang. While the research time was conducted in 2018. The population focused in this study were people who lived in the city of Padang and used the Gojek application with a sample of 160 people taken by purposive sampling. Data is processed using multiple linear regression method and data obtained from questionnaire results. From the results obtained from this study indicate that all dimensions of electronic service quality (E-S-Qual) have a direct relationship with customer loyalty at Î± = 0.05Keywords: E-S-qual; efficiency; system availability; fulfillment; privacy; customer loyalty